МЕТОДИКА ОЦЕНКИ ПЕРСПЕКТИВНОСТИ РЕГИОНАЛЬНЫХ ОБЪЕКТОВ ТУРИЗМА - Муканов, Б О (Journal of Economic Research & Business Administration, 2015)
In clause the technique of an estimation of prospect of regional objects of tourism is offered, in which basis the principles of regional economy, recreational and investment appeal with reference to conditions of Kazakhstan are fixed.